Extrapolating CIGS Module Performance From Laboratory Cell Performance Using IEC61853 Standard Reference Climatic Profiles - Vaas, T.S.; Pieters, B.E.; Friedlmeier, T. Magorian; Gerber, A.; Rau, U. (IEEE journal of photovoltaics, 2023)
In general, cell development and optimization is performed w.r.t. the cell performance parameters under standard test conditions (STC). However, as the performance of solar cells varies with temperature and irradiation, a single measurement at STC cannot reflect the performance of a device operated in various climatic conditions. In this article, we extrapolate module performance in various climates from cell performance verified at different conditions, i.e., we extrapolate module performance from the cell performance measured under various conditions. This way, and by employing the standardized climatic data provided by the IEC61853 norm, we are able to quickly determine the expected annual yield on module level under a wide variety of climatic conditions. Using this approach, we can assess which cell optimizations harbor the highest potential for yield improvements.